Implementasi Manajemen Kepala Sekolah Sebagai Motivator Dalam Meningkatkan Kualitas Kerja Guru - Anggraini, Helda Yusfarina; Ilyasin, Mukhamad; Muadin, Akhmad (El-Idare, 2023)
The success of the principal in managing his organization is not solely due to persistence, intelligence or expertise in a field but also depends on the success of his teacher in having productive and professional quality work. Lack of motivation can lead teachers to various problems such as being vulnerable to stress, loss of enthusiasm or enthusiasm for work and so on. Therefore, the role of the principal as a motivator must be turned on in order to improve the quality of teacher work. The purpose of this study is to examine further related to (1) school principal management as a motivator; and (2) the implementation of the principal's motivation for teachers. The research method used is a literature study obtained from internet searches related to previous research published from 2010-2021. Based on the findings, it was found that the provision of motivation from the principal to the teacher was given through positive motivation and negative motivation.